2010
DOI: 10.1016/j.ntt.2010.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Sexually dimorphic alterations in locomotion and reversal learning after adolescent tetrahydrocannabinol exposure in the rat

Abstract: Research suggests that use and abuse of marijuana can be especially harmful if it occurs during adolescence, a period of vast developmental changes throughout the brain. We examined the effects of 2 mg/kg Δ9-tetrahydrocannabinol (THC) administered daily via intra-peritoneal injections during juvenile/early adolescence (postnatal day 22–40) or late adolescence (postnatal day 41–60) on locomotor activity, development of tolerance, and acquisition/retention of spatial avoidance in adulthood. THC caused locomotor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 53 publications
5
38
1
Order By: Relevance
“…As demonstrated by previous results [47], the locomotor system may be equally sensitive during THC administration in males and females at this age. In contrast, the sexually differential effects of THC during drug abstinence may be caused by greater CB1 receptor desensitization and down-regulation in the striatum and PFC of adolescent female rats compared to male rats after chronic THC administration [75;76], causing a potential decrease in CB1 receptor activation by endocannabinoids in female rats during drug abstinence.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…As demonstrated by previous results [47], the locomotor system may be equally sensitive during THC administration in males and females at this age. In contrast, the sexually differential effects of THC during drug abstinence may be caused by greater CB1 receptor desensitization and down-regulation in the striatum and PFC of adolescent female rats compared to male rats after chronic THC administration [75;76], causing a potential decrease in CB1 receptor activation by endocannabinoids in female rats during drug abstinence.…”
Section: Discussionsupporting
confidence: 74%
“…The low dose of THC (2 mg/kg) was selected for use because this dose had previously been shown to produce effects on locomotor activity [47], but does not produce catalepsy, as is demonstrated by Wiley et al , [48]. Additionally, previous research conducted in our laboratory (see supplemental material) indicated peak plasma levels after a chronic dose of 2 mg/kg THC during adolescence to be 50–100 ng/mL in females, and 40–60 ng/mL in males.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have typically used rodents to characterize the long-term effects of chronic cannabinoid administration during adolescence in both males and females (Biscaia et al, 2003;Rubino et al, 2008Rubino et al, , 2009Harte and Dow-Edwards, 2010;Llorente-Berzal et al, 2011;Mateos et al, 2011;Winsauer et al, 2011Winsauer et al, , 2012Harte-Hargrove and Dow-Edwards, 2012). Male rats that received D 9 -tetrahydrocannabinol (THC) during adolescence made more errors during the acquisition of a radial-arm maze task than males that received vehicle (Rubino et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Our results also indicate that in the object location task, only the females showed a significantly impaired performance in response to adolescent (pnd 28-43) cannabinoid exposure, suggesting that diverse aspects of memory function may be differentially affected in each sex [57]. Treatment Harte and Dow-Edwards [97] examined the effects of THC administered daily during juvenile or early adolescence (pnd [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] or late adolescence (pnd 41-60) on locomotor activity, development of tolerance, and acquisition/retention of spatial avoidance in adulthood. THC causes locomotor depression in both male and female animals treated during early adolescence but only in females treated during late adolescence.…”
Section: Cannabis and Psychiatric Disorders-a Focus On Schizophreniamentioning
confidence: 60%